2022
DOI: 10.36764/ja.v6i1.753
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kepuasan Kerja Terhadap Kinerja Pegawai Dinas Perikanan Kabupaten Karo

Abstract: Job satisfaction is closely related to employee performance. This study aims to determine the effect of job satisfaction on the performance of the employees of the Karo Regency Fisheries Service. The sample in this study is a saturated sample so that all employees of the Karo Regency Fisheries Service as many as 37 people become subjects. Data were analyzed by simple linear regression analysis. Based on the calculations obtained the results of a simple linear regression equation; Y = 9.414+0.736X+e and the val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Representatives who land great position fulfillment typically have a decent record of participation, work turnover, and work execution, compared with representatives who don't land position fulfillment. (Sembiring et al, 2022) led research entitled The Impact of Occupation Fulfillment on the Exhibition of Workers at the Karo Rule Fisheries Administration. This study found that employees performance at the Karo Regency Fisheries Service was significantly influenced by job satisfaction.…”
Section: Literature Review / State-of-arts / Research Backgroundmentioning
confidence: 99%
“…Representatives who land great position fulfillment typically have a decent record of participation, work turnover, and work execution, compared with representatives who don't land position fulfillment. (Sembiring et al, 2022) led research entitled The Impact of Occupation Fulfillment on the Exhibition of Workers at the Karo Rule Fisheries Administration. This study found that employees performance at the Karo Regency Fisheries Service was significantly influenced by job satisfaction.…”
Section: Literature Review / State-of-arts / Research Backgroundmentioning
confidence: 99%
“…Menurut (Sembiring et al, 2021) kompensasi dapat diartikan sebagai imbalan yang diberikan oleh perusahaan kepada karyawan sebagai penghargaan atas pekerjaan yang sudah mereka lakukan. Kompensasi kerja yang memadai dapat membuat kepuasaan kerja karyawan, yang pada akhirnya dapat memberikan dampak positif terhadap kemampuan perusahaan untuk mempertahankan karyawan selama bekerja.…”
Section: Kompensasiunclassified
“…In the event that an individual has an uplifting outlook towards his work, he is happy with his work; on the other hand, in the event that a representative has a negative demeanor towards his work, he is disappointed with his work. Sembiring et al, (2022) led research entitled The Impact of Occupation Fulfillment on the Exhibition of Workers at the Karo Rule Fisheries Administration. This study found that employee's performance at the Karo Regency Fisheries Service was significantly influenced by job satisfaction.…”
Section: Introductionmentioning
confidence: 99%